2018
DOI: 10.1002/jcp.27575
|View full text |Cite
|
Sign up to set email alerts
|

Update on pathological platelet activation in coronary thrombosis

Abstract: Although coronary thrombosis (CT) is integral to cardiovascular outcomes, the underlying pathophysiological mechanisms remain unclear. CT may occur in case of atherosclerotic plaque erosion/rupture, or even after stenting implantation. Platelets (PLT) activation is the keystone of atherothrombosis and depends on many dysregulated elements, including endothelial dysfunction, oxidized lipoproteins, and immune response. Besides the classical view of PLT as an effector of hemostatic response, a new repertoire of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 127 publications
0
25
0
Order By: Relevance
“…Hyperglycaemia-mediated endothelial dysregulation has been recognized as a potential target for the treatment of cardiovascular disorders in patients with diabetes 15 . NLRP3 inflammasome activation has been shown to be involved in the pathogenesis of cardiovascular disease and vascular endothelial dysfunction 6 . IL-1β and IL-18, two key cytokines regulated by NLRP3 inflammasome activation, participate in endothelial inflammation and cardiovascular disease in humans 7,[16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperglycaemia-mediated endothelial dysregulation has been recognized as a potential target for the treatment of cardiovascular disorders in patients with diabetes 15 . NLRP3 inflammasome activation has been shown to be involved in the pathogenesis of cardiovascular disease and vascular endothelial dysfunction 6 . IL-1β and IL-18, two key cytokines regulated by NLRP3 inflammasome activation, participate in endothelial inflammation and cardiovascular disease in humans 7,[16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial NLRP3 inflammasome activation mediates endothelial inflammation 4,5 , thus resulting in vascular endothelial injury in hyperglycaemia 6 . The characteristics of the subjects are shown in Table 1.…”
Section: Nlrp3 Inflammasome Activation and Mark4 Increase In Diabeticmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [29] suggested that elevated glucose level is associated with the development of endothelial dysfunction. Moreover, this endothelial dysfunction is the leading cause of platelet activation [30]. In addition, hyperglycemia plays an important role in the development of diabetic macrovascular complications, including atherosclerosis and restenosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…This “Trojan horse” of lipid repertoire is overlooked in the conventional lipid profile but has profound pathophysiological significance. Platelets can deliver atherogenic lipids while seeding atheroprogression and contribute to chronic manifestations of cardiovascular disease (CVD) . Lately, advanced lipidomic analyses have started to unravel the multifaceted aspects of the platelet lipidome .…”
Section: Introductionmentioning
confidence: 99%